225k views
4 votes
Y = –2x + 14

y = 2x – 14

Y = –2x + 14 y = 2x – 14-example-1

1 Answer

1 vote

Answer:

(7, 0 )

Explanation:

Given the 2 equations

y = - 2x + 14 → (1)

y = 2x - 14 → (2)

Since both equations express y in terms of x we can equate them

2x - 14 = - 2x + 14 ( add 2x to both sides )

4x - 14 = 14 ( add 14 to both sides )

4x = 28 ( divide both sides by 2 )

x = 7

Substitute x = 7 into (2) for corresponding value of y

y = (2 × 7) - 14 = 14 - 14 = 0

Solution is (7, 0 )

User Sohum
by
5.8k points